Faktor-faktor yang mempengaruhi Keputusan pembelian halal food di E-commerce di Kota Salatiga - Winasa, Aprila Gusti; Saifudin, Saifudin (Journal of Halal Industry Studies, 2022)
This research is motivated by the public's interest in Islamic economics by introducing them to the halal food industry. Concerning the halal food industry, people have unique and distinctive consumption behaviors and preferences in consuming halal food. This study aimed to determine the effect of lifestyle, brand ambassador, product quality, halal label, and religiosity on purchasing decisions. The data used in this study are the people of Salatiga who have purchased halal food products on e-commerce sites. The analytical model used in this study is multiple regression and moderated regression analysis (MRA), with the number of respondents in this study being 100 Muslim consumers. The research output shows that the lifestyle variable does not affect purchasing decisions. A brand ambassador has no significant effect on purchasing decisions. Product quality has a significant positive effect on purchasing decisions. The halal label has a significant positive effect on purchasing decisions. Religion weakens the influence of lifestyle on purchasing decisions. Religiosity weakens the influence of brand ambassadors on purchasing decisions. Religiosity weakens the influence of product quality on purchasing decisions. Religiosity strengthens the influence of the halal label on purchasing decisions.